The Hausa 12-item short-form health survey (SF-12): Translation, cross-cultural adaptation and validation in mixed urban and rural Nigerian populations with chronic low back pain. - Aminu Alhassan Ibrahim; Mukadas Oyeniran Akindele; Sokunbi Oluwaleke Ganiyu; Bashir Kaka; Bashir Bello Abdullahi; Surajo Kamilu Sulaiman; Francis Fatoye (PLoS ONE, 2020)
Introduction Measuring health-related quality of life (HRQOL) in patients with chronic low back pain (LBP) is crucial to monitor and improve the patients' health status through effective rehabilitation. While the 12-item short-form health survey (SF-12) was developed as a shorter alternative to the 36-item short-form health survey for assessing HRQOL in large-scale studies, to date, no cross-culturally adapted and validated Hausa version exists. This study aimed to translate and cross-culturally adapt the SF-12 into Hausa language, and test its psychometric properties in mixed urban and rural Nigerian populations with chronic LBP. Methods The Hausa version of the SF-12 was developed following the guidelines of the International Quality of Life Assessment project. Fifteen patients with chronic LBP recruited from urban and rural communities of Nigeria pre-tested the Hausa SF-12. A consecutive sample of 200 patients with chronic LBP recruited from urban and rural clinics of Nigeria completed the instrument, among which 100 respondents re-tested the instrument after two weeks. Factorial structure and invariance were assessed using confirmatory factor analysis (CFA) and multi-group CFA respectively. Multi-trait scaling analysis (for convergent and divergent validity) and known-groups validity were performed to assess construct validity. Composite reliability (CR), internal consistency (Cronbach's α), intraclass correlation coefficients (ICC), and Bland-Altman plots were computed to assess reliability. Results After the CFA of the original conceptual SF-12 model, 2 redundant items were removed and 4 error terms were allowed to covary, thus providing adequate fit to the sample. The refined model demonstrated good fit and evidence of factorial invariance in three demographic groups (age, gender, and habitation). Convergent (11:12; 91% success rate) and divergent (10:12; 83% success rate) validity were satisfactory. Known-groups comparison showed that the instrument discriminated well for those who differed in age (p < 0.05) but in gender and habitation (p > 0.05). The physical component summary and the mental component summary demonstrated acceptable CR (0.69 and 0.79 respectively), internal consistency (α = 0.73 and 0.78 respectively), test-rest reliability (ICC = 0.79 and 0.85 respectively), and good agreement between test-retest values. Conclusions The Hausa SF-12 was successfully developed and showed evidence of factorial invariance across age, gender, and habitation. The instrument demonstrated satisfactory construct validity, internal consistency, and test-retest reliability. However, stronger psychometric properties need to be established in general population and other patients groups in future studies. The instrument can be used clinically and for research in Hausa-speaking patients with chronic LBP.